Revision of performance measurement tools and methods - Alladyn Elmgasbi (e-Finanse: Financial Internet Quarterly, 2019)
A changing economic environment and growing requirements of stakeholders have made it necessary to develop new achievement measurement methods. The article discusses and compares several performance measurement tools and methods, such as: theBalanced Scorecard, Tableau debord, Skandia Navigator, Intangible Assets Monitor, German Scorecard, Business Excellence Model, Dutch system of performance management, Performance Prism and the EFQM Excellence Model. They are the most popular among both theoreticians and practitioners in this field.
Keywords: G32; 330; Performance measurement; Balanced Scorecard; Tableau de bord de gestion; Skandia Navigator; Business Excellence Model; Performance Prism; EFQM